Best practices are never best: Evaluating primate conservation education programs (PCEPs) with a decolonial perspective. Issue 5 (3rd August 2022) - Bezanson, Michelle; Franquesa‐Soler, Montserrat; Kowalewski, Martin; McNamara, Allison; Oktaviani, Rahayu; Rodrigues, Michelle A.
Abstract: Who do we aim to educate with primate conservation education programs (PCEPs)? In a commentary published in a recent AJP, Annette Lanjouw suggested that many efforts to "educate" habitat‐country communities can be neocolonial in their approaches. Forest destruction and habitat loss are a result of global consumption and expansion. We therefore need to approach conservation education from many angles including local stakeholders, policy makers, government officials, and the humans living in industrialized nations who are major consumers of the items that shrink primate habitats. In this review, we investigate PCEPs to determine if the conservation education goals, education methods, and assessment processes are proceeding within a neocolonial context. We reviewed the last 20 years of primate conservation literature and looked for publications that were focused on education programs. We found that in 50 of 52 publications published between 2001 and 2021, the education programs take place in habitat‐country local communities. We also reviewed primate field researcher and field site websites, and in most cases, education programs were also focused on educating local communities living near or in nonhuman primate habitats. Exceptions were student clubs, zoo programs, and a high school outreach program. Many PCEP providers presented a list of "lessons learned" and we compiled their wisdom in combination with our experience to provide a framework for moving forward. We conclude that as conservation primatologists, we must think beyond our field sites to create opportunities for educational outreach. We can reach global consumers by linking to zoos, television/motion picture, print media, social media, and working with schools on curricula. Primatologists can engage our undergraduates to establish clubs and create meaningful assignments that reach beyond the classroom. We encourage primatologists from the Global North to consider their positionality and the history of conservation exclusion in their attempts to conserve primates. Abstract : Linking Conservation Goals to the Conservation Education Outcomes and Assessment Research Highlights: We surveyed the Primate Conservation Education Program (PCEP) published literature and online resources to deconstruct the recommendations, strengths and weaknesses of PCEPs. We collated information on lessons learned to provide a framework for moving forward. Global North primatologists who are interested in beginning a PCEP should first consider outreach and education in the Global North.